THE RELATIONSHIP OF THE WORK SAFETY PROGRAMS IMPLEMENTATION WITH THE PRODUCTIVITY OF EMPLOYEES IN PACKER PARTNERS PT. SEMEN BOSOWA MAROS - Ani Asriani Basri; Hasbi Ibrahim (Universitas Darussalam Gontor, 2018)
The application of work safety programs is one form of the company's efforts to create safe and healthy workplace conditions for the workforce, so as to reduce absenteeism and increase employee productivity.This study aims to find out how the